Regional development through industrial tourism: A systematic literature review - Montenegro, Z.; Marques, J.; Sousa, C. (Revista Portuguesa de Estudos Regionais, 2024)
This article contributes to a conceptual clarification and an understanding of how industrial tour-ism research has evolved. It is based on a literature review of scientific research produced over the past 25 years, focusing on its relation to regional development. The analysis was based on 51 scien-tific articles retrieved from the Scopus database. The growing interest in this theme, which is trans-versal to several research areas, is evident, adopting, in most cases, a qualitative methodology of case studies. As a promoter of regional development, industrial tourism has positive aspects, such as economic, social, and ecological benefits, among others, but also some constraints, such as ex-cessive commercialization and loss of authenticity of the places. Thus, this work also contributes to identifying this product's impacts and development strategies in the territories.